2020
DOI: 10.5194/amt-13-6473-2020
|View full text |Cite
|
Sign up to set email alerts
|

Best practices for precipitation sample storage for offline studies of ice nucleation in marine and coastal environments

Abstract: Abstract. Ice-nucleating particles (INPs) are efficiently removed from clouds through precipitation, a convenience of nature for the study of these very rare particles that influence multiple climate-relevant cloud properties including ice crystal concentrations, size distributions and phase-partitioning processes. INPs suspended in precipitation can be used to estimate in-cloud INP concentrations and to infer their original composition. Offline droplet assays are commonly used to measure INP concentrations in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…This process starts with the formation of cloud droplet followed by freezing due to an INP immersed in the supercooled droplet. In addition, past studies have identified other modes of heterogeneous nucleation, such as condensation freezing (Belosi and Santachiara, 2019), contact freezing (Hoffmann et al, 2013), and inside-out evaporation freezing (Durant and Shaw, 2005). These modes are relatively less relevant in mixed-phase clouds (MPCs) as discussed in the next section.…”
Section: What Are Inps?mentioning
confidence: 94%
“…This process starts with the formation of cloud droplet followed by freezing due to an INP immersed in the supercooled droplet. In addition, past studies have identified other modes of heterogeneous nucleation, such as condensation freezing (Belosi and Santachiara, 2019), contact freezing (Hoffmann et al, 2013), and inside-out evaporation freezing (Durant and Shaw, 2005). These modes are relatively less relevant in mixed-phase clouds (MPCs) as discussed in the next section.…”
Section: What Are Inps?mentioning
confidence: 94%
“…Water losses due to evaporation were compensated for by replenishing the circulating water after 10 and 20 min. To avoid storage effects (Beall et al, 2020), samples were analysed immediately after collection in a drop-freezing assay with 52 droplets of 100 µL each, as previously described (Stopelli et al, 2014), and cumulative [INP] was calculated (Vali, 1971). Sampling and analysis were designed in such a way that expected [INP −15 ] of each sample would be well within the detection limits, meaning that several but not all droplets in the assay would be frozen.…”
Section: Methodsmentioning
confidence: 99%
“…DeMott et al, 2010;Phillips et al, 2013) are based. Furthermore, an increase in atmospheric abundance of INPs active at moderate supercooling has been observed during precipitation (Bigg and Miles, 1964;Huffman et al, 2013;Hara et al, 2016;Conen et al, 2017). This might be explained by aerosolisation of INPs by rain itself, a mechanism similar to the generation of bioaerosol by raindrop impingement (Joung et al, 2017), which is probably dependent on various parameters like surface wetness or land cover.…”
Section: Introductionmentioning
confidence: 98%
“…A prime limitation for the absence of longterm monitoring data sets was that online real-time measurements of INP concentrations via INP counters required human operators, as no autonomous online INP counter were available. Bi et al (2019) presented the first autonomous online INP counter based on a continuous flow thermal gradient diffusion chamber (CFDC). A novel paper by Möhler et al (2020) introduced the Portable Ice Nucleation Experiment (PINE), an autonomous online INP counter that uses the adiabatic cooling during expansion to activate the INPs at the targeted supersaturation.…”
Section: Introductionmentioning
confidence: 99%